IMPLEMENTASI MEDIA POHON BILANGAN DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS V SDN 2 PRAYA - Ningrum, Anisya Sulistya; Darmiany; Radiusman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of instructional media is essential at the elementary school level because students are still in the concrete operational stage of cognitive development and require concrete learning aids to better understand mathematical concepts and solve problems. Therefore, this study implemented the Number Tree learning media in mathematics instruction for fifth-grade students at SDN 2 Praya. This research employed a qualitative approach using a descriptive research design. The participants consisted of 35 fifth-grade students. Data were collected through classroom observations, interviews, and documentation conducted over four learning sessions at SDN 2 Praya. The data were analyzed using data reduction, data display, and conclusion drawing techniques, while data validity was ensured through triangulation. The findings revealed that the implementation of the Number Tree learning media had a positive impact on students' mathematical understanding, particularly in the topics of the Greatest Common Divisor (GCD) and the Least Common Multiple (LCM). Students who initially experienced difficulties in understanding these concepts were able to determine the GCD and LCM of given numbers more accurately after using the learning media.